Performance Analysis of Real Time Image Processing for Lightning Event Using Cython and Python Programming Languages - Mun S.H.; Ahmad M.R.; Malik R.F.; Esa M.R.M.; Sabri M.H.M.; Periannan D.; Seah B.Y.; Mohamad S.A.; Cooray V.; Alkahtani A.A.; Kadir M.Z.A.A.B. (Institute of Physics Publishing, 2023)
Climate change; Electromagnetic fields; High speed cameras; Lightning; Electromagnetic signals; Lightning detection methods; Performance analysis; Public safety; Python programming language; Real-time image processing; Research process; Research topics; Image processing